RISK FACTORS FOR HUMERAL HEAD OSTEONECROSIS IN PATIENTS WITH PROXIMAL HUMERAL FRACTURES TREATED OPERATIVELY - Konstantin Totev; Georgi Dimitrov; Lyubomira Toteva; Svilen Todorov; Steliyan Lungarov (Journal of IMAB, 2021)
Proximal humerus presents the second most frequent site of posttraumatic osteonecrosis. This complication is usually related to poor functional outcomes. The aim of this study is to identify and analyze the risk factors for posttraumatic humeral head osteonecrosis in surgically treated patients. Ninety-one patients with 92 acute proximal humeral fractures were operated on for a period of 39 months. Operative methods include open reduction and internal fixation and closed reduction and percutaneous fixation. Fractures were classified according to Neer, AO and LEGO classifications. The mean age of patients was 60.9 years. From 91 operated patients for follow-up were available 82. The mean follow-up period was 15 months. Patient data was collected prospectively. Functional results are present using age and gender adjusted Constant score. In 41 patients, the result is excellent, in 28-good, in 11-fair and in 3 poor. Bone union was evident in all cases. No deep wound infections, nerve injuries, vascular injuries and implant failure were observed. Osteonecrosis was seen in 5 (6.1%) patients. Patients with posttraumatic osteonecrosis had significant lower Constant results. Analyzing the pre- and intraoperative factors in patients with osteonecrosis, we find that the most significant factors for this complication are increasing fracture severity and а combination of short medial metaphyseal extension and disrupted medial hinge.